Comparison of the perceived subjective exertion and total load lifted response in resistance exercises performed on stable and unstable platforms - Liliane Cunha Aranda; Marcelly Mancini; Yuri Almeida Costa Campos; Elder Dutra Sousa; Jeferson Macedo Vianna; Marzo Edir Da Silva-Grigoletto (Universidade Federal de Santa Catarina, 2015)
This study aimed to compare the perceived subjective exertion (PSE) and total load lifted in resistance exercises performed on stable platforms (SP) and unstable platforms (UP). Participants were 20 men (24.6 ± 3.4 years, 179 ± 0.1 cm, 80.6 ± 9.1 kg and 11.8 ± 3.4% fat). Each subject performed a 15 maximum repetition test in half squat exercises (soil and balance discs), pronated barbell row (soil and bosu) and biceps curl (soil and balance discs) in both conditions. PSE was measured using the OMNI-RES scale and the load lifted value (kg). To verify the normality of data, the Shapiro-Wilk test was used. Possible differences related to loads and PSE on the platforms were performed by the paired t test. Significance level of p <0.05 was adopted. No significant differences between PSE values on SP and UP were respectively observed in the half squat (8.2 and 8.5 / p = 0.8), pronated barbell row (8.4 and 8.4 / p = 0.7) and biceps curl (8.6 and 8.7 / p = 1.0). Higher load values on SP and UP were respectively found in half squat (83.9kg and 70.3kg / p <0.001) and pronated barbell row exercises (53.2kg and 48.6kg / p = 0.01) on SP. However, biceps curl showed dissimilar behavior (48.2kg and 47.4kg / p = 0.5). It was concluded that UP does not promote differences in PSE responses even working with smaller load or similar load.